Post-lockdown management of oncological priorities and postponed radiation therapy following the COVID-19 pandemic: Experience of the Institut Curie. (September 2020) - Beddok, Arnaud; Calugaru, Valentin; Minsat, Mathieu; Dendale, Rémi; De Oliveira, Aurélien; Costa, Émilie; Goudjil, Farid; Belshi, Rezart; Pierrat, Noelle; Rochas, Christophe; Gravigny, Anne Catherine; Soisick, Lucas; et al.
Highlights: During COVID-19 lockdown, the number of radiotherapy treatments had to be reduced. Given number of delayed treatments, the post-crisis period should be anticipated. Data visualization software allowed to predict when peak activity would happen.